FRI0235 Incidence of Paradoxical Reactions in Patients with Rheumatoid Arthritis during Tocilizumab Therapy: Data from The French Registry Regate. (15th July 2016) - Terreaux, W.; Eschard, J.-P.; Wendling, D.; Marcelli, C.; Perdriger, A.; Collet, P.; Le Dantec, L.; Constantin, A.; Scotto Di Fazano, C.; Bardin, T.; Sibilia, J.; Morel, J.; et al.
Abstract : Background: Tocilizumab is a humanized monoclonal antibody specific to the alpha subunit of the receptor of interleukin-6 (IL-6) indicated in the management of some rheumatic diseases. The monitoring of patients under biotherapy has led to the discovery of particular side effects called paradoxical effects, that is to say, conditions that are supposed to be treated with the biotherapy itself [1–2]. To our knowledge, there is no clinical trial or "real life" data assessing the occurrence of paradoxical effects under tocilizumab therapy from a large cohort. Objectives: To assess the frequency of paradoxical effects encountered in everyday practice under tocilizumab therapy, using the REGATE (Registry-RoActemra) registry [3]. The secondary objectives are to determine the type of paradoxical effect and the consequences of these effects. Methods: The REGATE registry is an independent prospective registry, promoted by the French Society of Rheumatology, consisting of patients with rheumatoid arthritis treated by tocilizumab. For every paradoxical reaction, the data was validated by the clinician in charge of the patient. The paradoxical effect was noted if the induced pathology appeared after exposure to at least one tocilizumab infusion, and if tocilizumab was likely to treat the condition in question [4]. If patients had one of these conditions de novo while under tocilizumab therapy for another condition, we considered it as a paradoxical effect. The aggravation of a preexisting condition was also considered as a paradoxical effect [1]. Results: Among the 1499 patients included with at least one follow-up visit (3429 patient-years), a paradoxical reaction occurred in 14 patients (0.93% of patients; 4.08/1000 patient-years). These were 10 de novo pathologies (3 vasculitis, 3 uveitis, 2 psoriasis, 1 lupus, 1 ulcerative colitis) and 4 exacerbations of pre-existing conditions (2 psoriasis, 1 vasculitis, 1 lupus). The average time between the initiation of tocilizumab and the appearance of the first manifestation of the paradoxical effect was 14.85 (±12.79) months. Permanent discontinuation of tocilizumab was chosen for 5 patients (35%), a transitional stop for 3 patients, a dosage adjustment for 1 patient. One paradoxical effect (psoriasis) recurred with continued tocilizumab. Conclusions: Paradoxical reactions under tocilizumab are not frequent (less than 1%) but require an adaptation of treatment in over 50% of cases. References: Wendling D, Prati C. Paradoxical effects of anti-TNF-α agents in inflammatory diseases. Expert Rev Clin Immunol. 2014. Fouache D, Goëb V, et al. Paradoxical adverse events of anti-tumour necrosis factor therapy for spondyloarthropathies: a retrospective study. Rheumatology (Oxford). 2009. Mariette X, Gottenberg JE, et al. Registries in rheumatoid arthritis and autoimmune diseases: data from the French registries. Rheumatology (Oxford). 2011. Mesquida M, Leszczynska A, et al. Interleukin-6 blockade in ocular inflammatory diseases. Clin Exp Immunol. 2014. Disclosure of Interest: None declared